Do you not know what it is a canon? Challenges to establish a Peruvian symphonic canon - Junchaya Rojas, Rafael Leonardo (2023)
In the description of musical canon introduced by Marcia Citron, the presence of certain features and agents is necessary for its formation. In the case of a Peruvian symphonic or orchestral musical canon, these agents and features produce challenges, some of which are not easy to overcome. This paper describes and discusses such challenges, within Citron’s model of musical canon, showing the complications to assume the task. The Peruvian symphonic canon is still in formation, at least from an academic point of view.